2009
DOI: 10.1017/s0950268809990896
|View full text |Cite
|
Sign up to set email alerts
|

Micro and macro population effects in disease transmission: the case of varicella

Abstract: SUMMARYProfiles of varicella-zoster virus (VZV) seroprevalence have shown large variability in European countries in which vaccination has not been implemented. Differences in micro and macro population structures (e.g. household and municipality, respectively) may explain such variability, which is the focus of a population-based study of varicella in 12 000 children from 7800 French households in Corsica. The cumulative incidence was 89 % at age 11 years, as the median age at infection was 5 years in first-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 31 publications
4
17
0
Order By: Relevance
“…Some studies have reported that living in urban areas, living in a large family (≥ 4 people) and children with more siblings are factors associated with higher varicella seroprevalence. Many studies have found no gender difference for varicella seroprevalence (2,3,16,17,(28)(29)(30). Consistent with the current study, varicella seroprevalence was not associated with household size, income, occupation and education in a population-based study in Izmir in 2009-2010 (16).…”
Section: Discussionsupporting
confidence: 89%
“…Some studies have reported that living in urban areas, living in a large family (≥ 4 people) and children with more siblings are factors associated with higher varicella seroprevalence. Many studies have found no gender difference for varicella seroprevalence (2,3,16,17,(28)(29)(30). Consistent with the current study, varicella seroprevalence was not associated with household size, income, occupation and education in a population-based study in Izmir in 2009-2010 (16).…”
Section: Discussionsupporting
confidence: 89%
“…This probably reflects different country-specific dynamics in varicella transmission during childhood, which have been associated with differences in social mixing patterns [12, 13]. Countries with low incidence rates in children <5 years of age have higher incidence rates in older age groups.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, we built a linear regression model based on the incidences in the younger age groups and country-level prediction variables that have been shown to be associated with country-level differences in varicella transmissibility and health care use [12, 13] (Additional file 2): proportion of children <3 years that receive no formal childcare [14], population density [14], inequality in income distribution [14], proportion of people at risk of poverty [14], total health expenditure [15], proportion of households with 1, 2, 3, and 4 or more children [14], number of annual consultations of a medical doctor per inhabitant [14], and number of acute hospital discharges per 100 population [14]. …”
Section: Methodsmentioning
confidence: 99%
“…Other studies have described that anti-VZV seroprevalence may be related to household composition (≥ 4 persons) and school attendance by a household member [3,6,28-30] . However, in this study no association between anti-VZV seroprevalence and having children or the number of children was found.…”
Section: Discussionmentioning
confidence: 99%